1974
DOI: 10.1212/wnl.24.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antithymocyte globulin in acute relapses of multiple sclerosis

Abstract: The findings in this study indicate that therapy with a combination of ACTH and antithymocyte globulin (ATG) should be strongly considered for patients with multiple sclerosis who are in acute relapse, who have an elevation in the ratio of gamma globulin to total protein in cerebrospinal fluid, and who are not responsive to ACTH or corticosteroid alone. Twenty-one patients with acute bouts of multiple sclerosis were randomly allocated and treated under controlled conditions with ACTH alone or ACTH and ATG. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The original study used ATG in comparable dosage to that used in intensive immunosuppression, and it was beneficial on a short term basis in acute relapsing M.S. (Seland et al, 1974). Furthermore, the trial found that patients with an elevated gamma globulin to total protein ratio ( > 14%) in their C.S.F.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The original study used ATG in comparable dosage to that used in intensive immunosuppression, and it was beneficial on a short term basis in acute relapsing M.S. (Seland et al, 1974). Furthermore, the trial found that patients with an elevated gamma globulin to total protein ratio ( > 14%) in their C.S.F.…”
Section: Discussionmentioning
confidence: 99%
“…This study re-evaluated patients five years after they were treated with ATG. The results of the original prospective study, which included a one year follow-up, have been reported (Seland et al, 1974).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, even when proper randomization was accomplished, stratification techniques were generally ignored. As a consequence, important differences occurred in the treatment and control groups in terms of age of onset and age of entry (Hauser et al, 1983), age at entry and duration of disease (Seland et al, 1974), degree of disability (Mertin et al, 1983) and relapse rate (Jacobs et al, 1982).…”
Section: Clinical Trial Experiencementioning
confidence: 99%